Evaluation of wood carving skills for students of the department Family education and artistic professions (Journal of the College of Basic Education, 2022)
Man has introduced several techniques to the raw material of wood, including the perforation technique, with which he has always excelled. He mastered his work with engravings, resulting in a kind of art that is self-standing and exciting for the human psyche.Which required a manual skill with the interaction of mental and physical activity to deal with mathematical proportions. And dealing with the aesthetic aspects, and thus achieving his ability for the learner with a balance between the cognitive aspects. physical and functional. There is no doubt that evaluation leads to identifying the technical performance skills acquired by the learner. And standing at the points of strength and weakness in all materials, including wood perforation.